2018
DOI: 10.2196/jmir.8922
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Just-in-Time Information and Feedback on Antibiotic Use for Village Doctors in Rural Anhui, China: Randomized Controlled Trial

Abstract: BackgroundExcessive use of antibiotics is very common worldwide, especially in rural China; various measures that have been used in curbing the problem have shown only marginal effects.ObjectiveThe objective of this study was to test an innovative intervention that provided just-in-time information and feedback (JITIF) to village doctors on care of common infectious diseases.MethodsThe information component of JITIF consisted of a set of theory or evidence-based ingredients, including operation guideline, publ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…A promising recent example in Anhui province, China, was able to provide 'just-intime' individualised information and feedback to doctors Open access in village clinics which improved antibiotic prescribing practices. 43…”
Section: Resultsmentioning
confidence: 99%
“…A promising recent example in Anhui province, China, was able to provide 'just-intime' individualised information and feedback to doctors Open access in village clinics which improved antibiotic prescribing practices. 43…”
Section: Resultsmentioning
confidence: 99%
“…Inappropriate use of antibiotics is influenced by nonbiomedical factors within and beyond clinical settings that are unique to mainland China, yet common among lowincome and middle-income countries, including public misconceptions, 16-18 22 28 31 35 36 43 57 59 habitual use without professional guidance, 58 insufficient FDA monitoring, 56 incentivising the healthcare system towards prescribing and selling, 23 24 56 lack of diagnostic capacity, 25 27 and the delicate relationships between patients and prescribers, 27 but some critical factors such as antibiotic literacy remained as research gaps. To date, there have been only few interventions implemented in primary care settings to reduce inappropriate prescribing, [64][65][66][67][68][69][70] largely targeting clinicians and ignoring demand-side factors. Further, more research is needed to investigate the associations between human and animal use of antibiotics in rural China, where 564 million people reside 71 in order to inform effective One Health interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Another survey of prescriptions from village clinics in middle-east China showed that the proportion of antibiotics prescribed for respiratory tract infections (RTIs) accounted for 87% [7] . The Chinese government has introduced a number of regulations to control antibiotic use in the last decade, but these have not played a signi cant role in rural areas [8] .…”
Section: Introductionmentioning
confidence: 99%